A 3D In Vivo Model for Studying Human Renal Cystic Tissue and Mouse Kidney Slices - Bichlmayer, Eva Marie; Mahl, Lina; Hesse, Leo; Pion, Eric; Haller, Victoria; Moehwald, Andreas; Hackl, Christina; Werner, Jens M.; Schlitt, Hans J.; Schwarz, Siegfried; Kainz, Philipp; Brochhausen, Christoph; et al. (Cells, 2022)
(1) Background: Autosomal dominant polycystic kidney disease (ADPKD) is a frequent monogenic disorder that leads to progressive renal cyst growth and renal failure. Strategies to inhibit cyst growth in non-human cyst models have often failed in clinical trials. There is a significant need for models that enable studies of human cyst growth and drug trials. (2) Methods: Renal tissue from ADPKD patients who received a nephrectomy as well as adult mouse kidney slices were cultured on a chorioallantoic membrane (CAM) for one week. The cyst volume was monitored by microscopic and CT-based applications. The weight and angiogenesis were quantified. Morphometric and histological analyses were performed after the removal of the tissues from the CAM. (3) Results: The mouse and human renal tissue mostly remained vital for about one week on the CAM. The growth of cystic tissue was evaluated using microscopic and CT-based volume measurements, which correlated with weight and an increase in angiogenesis, and was accompanied by cyst cell proliferation. (4) Conclusions: The CAM model might bridge the gap between animal studies and clinical trials of human cyst growth, and provide a drug-testing platform for the inhibition of cyst enlargement. Real-time analyses of mouse kidney tissue may provide insights into renal physiology and reduce the need for animal experiments.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 3D in vivo model; ADPKD; chorioallantoic membrane (CAM) model; human renal cystic tissue; mouse kidney slices; polycystic kidney disease

Anoctamin 6 is localized in the primary cilium of renal tubular cells and is involved in apoptosis-dependent cyst lumen formation - Forschbach, V.; Goppelt-Strübe, Margarete; Kunzelmann, K.; Schreiber, R.; Piedagnel, Remi; Kraus, Andre; Eckardt, Kai-Uwe; Buchholz, Björn (Cell Death & Disease, 2015)
Primary cilia are antenna-like structures projected from the apical surface of various mammalian cells including renal tubular cells. Functional or structural defects of the cilium lead to systemic disorders comprising polycystic kidneys as a key feature. Here we show that anoctamin 6 (ANO6), a member of the anoctamin chloride channel family, is localized in the primary cilium of renal epithelial cells in vitro and in vivo. ANO6 was not essential for cilia formation and had no effect on in vitro cyst expansion. However, knockdown of ANO6 impaired cyst lumen formation of MDCK cells in three-dimensional culture. In the absence of ANO6, apoptosis was reduced and epithelial cells were incompletely removed from the center of cell aggregates, which form in the early phase of cystogenesis. In line with these data, we show that ANO6 is highly expressed in apoptotic cyst epithelial cells of human polycystic kidneys. These data identify ANO6 as a cilium-associated protein and suggest its functional relevance in cyst formation.

A novel direct adenosine monophosphate kinase activator ameliorates disease progression in preclinical models of Autosomal Dominant Polycystic Kidney Disease - Dagorn, Pascale Gluais; Buchholz, Björn; Kraus, Andre; Batchuluun, Battsetseg; Bange, Hester; Blockken, Laura; Steinberg, Gregory R.; Moller, David E.; Hallakou-Bozec, Sophie (Kidney International, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) mainly results from mutations in the PKD1 gene, which encodes polycystin 1. It is the most common inherited kidney disease and is characterized by a progressive bilateral increase in cyst number and size, often leading to kidney failure. The cellular energy sensor and regulator adenosine monophosphate stimulated protein kinase (AMPK) has been implicated as a promising new therapeutic target. To address this hypothesis, we determined the effects of a potent and selective clinical stage direct allosteric AMPK activator, PXL770, in canine and patient-derived 3D cyst models and an orthologous mouse model of ADPKD. PXL770 induced AMPK activation and dose-dependently reduced cyst growth in principal-like Madin-Darby Canine Kidney cells stimulated with forskolin and kidney epithelial cells derived from patients with ADPKD stimulated with desmopressin. In an inducible, kidney epithelium-specific Pkd1 knockout mouse model, PXL770 produced kidney AMPK pathway engagement, prevented the onset of kidney failure (reducing blood urea by 47%), decreased cystic index by 26% and lowered the kidney weight to body weight ratio by 35% compared to untreated control Pkd1 knockout mice. These effects were accompanied by a reduction of markers of cell proliferation (-48%), macrophage infiltration (-53%) and tissue fibrosis (-37%). Thus, our results show the potential of direct allosteric AMPK activation in the treatment of ADPKD and support the further development of PXL770 for this indication.
CRIS-Team Scopus Importer:2023-04-21
Keywords: ADPKD; AMPK; fibrosis; inflammation; mitochondria; PXL770

Cyst growth in ADPKD is prevented by pharmacological and genetic inhibition of TMEM16A in vivo - Cabrita, Ines; Kraus, Andre; Scholz, Julia Katharina; Skoczynski, Kathrin; Schreiber, Rainer; Kunzelmann, Karl; Buchholz, Björn (Nature Communications, 2020)
In autosomal dominant polycystic kidney disease (ADPKD) multiple bilateral renal cysts gradually enlarge, leading to a decline in renal function. Transepithelial chloride secretion through cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1) are known to drive cyst enlargement. Here we demonstrate that loss of Pkd1 increased expression of TMEM16A and CFTR and Cl− secretion in murine kidneys, with TMEM16A essentially contributing to cyst growth. Upregulated TMEM16A enhanced intracellular Ca2+ signaling and proliferation of Pkd1-deficient renal epithelial cells. In contrast, increase in Ca2+ signaling, cell proliferation and CFTR expression was not observed in Pkd1/Tmem16a double knockout mice. Knockout of Tmem16a or inhibition of TMEM16A in vivo by the FDA-approved drugs niclosamide and benzbromarone, as well as the TMEM16A-specific inhibitor Ani9 largely reduced cyst enlargement and abnormal cyst cell proliferation. The present data establish a therapeutic concept for the treatment of ADPKD.
CRIS-Team Scopus Importer:2020-09-04

Glucose promotes secretion-dependent renal cyst growth. - Kraus, Andre; Schley, Gunnar; Kunzelmann, Karl; Schreiber, Rainer; Peters, Dorien J. M.; Stadler, Ruth; Eckardt, Kai-Uwe; Buchholz, Björn (Journal of Molecular Medicine, 2016)
Polycystic kidney diseases are characterized by the development of numerous bilateral renal cysts that continuously enlarge resulting in a decline of kidney function due to compression of intact nephrons. Cyst growth is driven by transepithelial chloride secretion which depends on both intracellular cAMP and calcium. Mechanisms that are involved in the regulation of the underlying secretory pathways remain incompletely understood. Here we show that glucose concentration has a strong impact on cyst growth of renal tubular cells within a collagen matrix as well as in embryonic kidneys deficient or competent for Pkd1. Glucose-dependent cyst growth correlates with the transcriptional induction of the calcium-activated chloride channel anoctamin 1 (ANO1) and its increased expression in the apical membrane of cyst-forming cells. Inhibition of ANO1 with the specific inhibitor CaCCinh-AO1 significantly decreases glucose-dependent cyst growth in both models. Ussing chamber analyses revealed increased apical chloride secretion of renal tubular cells upon exposure to high glucose medium which can also be inhibited by the use of CaCCinh-AO1. These data suggest that glycemic control may help to reduce renal cyst growth in patients with polycystic kidney disease.Renal cyst growth depends on glucose concentration in two in vitro cyst models. High glucose leads to upregulation of the calcium-activated chloride channel ANO1. High glucose promotes calcium-activated chloride secretion via ANO1. Glucose-dependent secretion can be inhibited by a specific inhibitor of ANO1.
EVALuna2:3791
Keywords: Polycystic kidney disease; Cyst growth; Chloride secretion; Glucose; Diabetes mellitus type 2; Anoctamin 1

HIF-1α promotes cyst progression in a mouse model of autosomal dominant polycystic kidney disease - Kraus, Andre; Peters, Dorien J. M.; Klanke, Bernd; Weidemann, Alexander; Willam, Carsten; Schley, Gunnar; Kunzelmann, Karl; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2018)
Autosomal dominant polycystic kidney disease (ADPKD) is mainly caused by mutations of the PKD1 gene and characterized by growth of bilateral renal cysts. Cyst growth is accompanied by regional hypoxia and induction of hypoxia-inducible factor (HIF)-1α in cyst-lining epithelial cells. To determine the relevance of HIF-1α for cyst growth in vivo we used an inducible kidney epithelium-specific knockout mouse to delete Pkd1 at postnatal day 20 or 35 to induce polycystic kidney disease of different severity and analyzed the effects of Hif-1α co-deletion and HIF-1α stabilization using a prolyl-hydroxylase inhibitor. HIF-1α expression was enhanced in kidneys with progressive cyst growth induced by early Pkd1 deletion, but unchanged in the milder phenotype induced by later Pkd1 deletion. Hif-1α co-deletion significantly attenuated cyst growth in the severe, but not in the mild, phenotype. Application of a prolyl-hydroxylase inhibitor resulted in severe aggravation of the mild phenotype with rapid loss of renal function. HIF-1α expression was associated with induction of genes that mediate calcium-activated chloride secretion. Thus, HIF-1α does not seem to play a role in early cyst formation, but accelerates cyst growth during progressive polycystic kidney disease. This novel mechanism of cyst growth may qualify as a therapeutic target.
EVALuna2:215684
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; polycystic kidney disease; prolyl-hydroxylase inhibitors

Hypoxia induces polycystin-1 expression in the renal epithelium - Grampp, Steffen; Kraus, Andre; Skoczynski, Kathrin; Schiffer, Mario; Krüger, René; Naas, Stephanie; Schödel, Johannes; Buchholz, Björn (Royal Society Open Science, 2023)
Mutations in polycystin-1 which is encoded by the PKD1 gene are the main causes for the development of autosomal dominant polycystic kidney disease. However, only little is known about the physiological function of polycystin-1 and even less about the regulation of its expression. Here, we show that expression of PKD1 is induced by hypoxia and compounds that stabilize the hypoxia-inducible transcription factor (HIF) 1α in primary human tubular epithelial cells. Knockdown of HIF subunits confirms HIF-1α-dependent regulation of polycystin-1 expression. Furthermore, HIF ChIP-seq reveals that HIF interacts with a regulatory DNA element within the PKD1 gene in renal tubule-derived cells. HIF-dependent expression of polycystin-1 can also be demonstrated in vivo in kidneys of mice treated with substances that stabilize HIF. Polycystin-1 and HIF-1α have been shown to promote epithelial branching during kidney development. In line with these findings, we show that expression of polycystin-1 within mouse embryonic ureteric bud branches is regulated by HIF. Our finding links expression of one of the main regulators of accurate renal development with the hypoxia signalling pathway and provides additional insight into the pathophysiology of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-06-30
Keywords: hypoxia; hypoxia-inducible factor; kidney development; PKD1; polycystic kidney disease; transcription regulation

Hypoxia inhibits nephrogenesis through paracrine Vegfa despite the ability to enhance tubulogenesis - Schley, Gunnar; Scholz, Holger; Kraus, Andre; Hackenbeck, Thomas; Klanke, Bernd; Willam, Carsten; Wiesener, Michael; Heinze, Eva; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2015)
Reduced nephron number predisposes to hypertension and kidney disease. Interaction of the branching ureteric bud and surrounding mesenchymal cells determines nephron number. Since oxygen supply may be critical for intrauterine development, we tested whether hypoxia and hypoxiainducible factor-1 alpha (HIF-1 alpha) influence nephrogenesis. We found that HIF-1 alpha is required for branching of MDCK cells. In addition, culture of metanephric mouse kidneys with ureteric bud cell-specific stabilization or knockout of HIF-1 alpha revealed a positive impact of HIF-1 alpha on nephrogenesis. In contrast, widespread stabilization of HIF-1 alpha in metanephric kidneys through hypoxia or HIF stabilizers impaired nephrogenesis, and pharmacological HIF inhibition enhanced nephrogenesis. Several lines of evidence suggest an inhibitory effect through the hypoxia response of mesenchymal cells. HIF-1 alpha was expressed in mesenchymal cells during nephrogenesis. Expression of the anti-branching factors Bmp4 and Vegfa, secreted by mesenchymal cells, was increased upon HIF stabilization. The conditioned medium from hypoxic metanephric kidneys inhibited MDCK branching, which was partially rescued by Vegfa antibodies. Thus, the effect of HIF-1 alpha on nephrogenesis appears context dependent. While HIF-1 alpha in the ureteric bud is of importance for proper branching morphogenesis, the net effect of hypoxia-induced HIF activation in the embryonic kidney appears to be mesenchymal cell-dependent inhibition of ureter branching.
EVALuna2:3775
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; kidney development; metanephric mesenchyme; nephrogenesis; Vegfa

In vitro cyst puncture and injury-induced tubule formation using renal epithelial cells - Kraus, Andre; Lüdke, Andrea; Teschemacher, Barbara; Skoczynski, Kathrin; Buchholz, Björn (STAR Protocols, 2023)
Collecting-duct-derived renal epithelial cells switch from tubule to cyst formation; however, the cysts still form tubules after injury of the cyst-lining epithelium. Here, we provide a protocol that describes in vitro cyst growth with focus on glass-capillary-induced cyst wall injury to induce tubule formation. We detail steps for the establishment of the in vitro cyst assay, followed by puncture of the cysts in the collagen matrix. We further describe live imaging and steps to analyze the tubule growth. For complete details on the use and execution of this protocol, please refer to Scholz et al. (2022).1
CRIS-Team Scopus Importer:2023-02-03
Keywords: Cell Biology; Cell culture; Cell-based Assays; Microscopy

Lipid Peroxidation Drives Renal Cyst Growth In Vitro through Activation of TMEM16A - Schreiber, Rainer; Buchholz, Björn; Kraus, Andre; Schley, Gunnar; Scholz, Julia; Ousingsawat, Jiraporn; Kunzelmann, Karl (Journal of the American Society of Nephrology, 2019)
Background Transepithelial chloride2 secretion, through the chloride channels cystic fibrosis transmembrane conductance regulator (CFTR) and TMEM16A (anoctamin 1), drives cyst enlargement in polycystic kidney disease (PKD). Polycystic kidneys are hypoxic, and oxidative stress activates TMEM16A. However, mechanisms for channel activation in PKD remain obscure.Methods Using tissue samples from patients with autosomal dominant PKD, embryonic kidney cultures, and anMDCK in vitro cyst model, we assessed peroxidation of plasmamembrane phospholipids in human and mouse polycystic kidneys. We also used electrophysiologic Ussing chamber and patch clamp experiments to analyze activation of TMEM16A and growth of renal cysts.Results Peroxidation of phospholipids in human and mouse kidneys as well as MDCK cysts in vitro is probably due to enhanced levels of reactive oxygen species. Lipid peroxidation correlated with increased cyst volume as shown in renal cultures and MDCK cysts in three-dimensional cultures. Reactive oxygen species and lipid peroxidation strongly activated TMEM16A, leading to depletion of calciumion stores and store-operated calcium influx. Activation of TMEM16A-and CFTR-dependent chloride secretion strongly augmented cyst growth. Exposure to scavengers of reactive oxygen species, such as glutathione, coenzyme Q10, or idebenone (a synthetic coenzyme Q10 homolog), as well as inhibition of oxidative lipid damage by ferrostatin-1 largely reduced activation of TMEM16A. Inhibition of TMEM16A reduced proliferation and fluid secretion in vitro.Conclusions These findings indicate that activation of TMEM16A by lipid peroxidation drives growth of renal cysts. We propose direct inhibition of TMEM16A or inhibition of lipid peroxidation as potentially powerful therapeutic approaches to delay cyst development in PKD.
CRIS-Team WoS Importer:2019-02-27
Keywords: ADPKD; TMEM16A; reactive oxygen species; lipid peroxidation; ferroptosis; anoctamin 1

Loss of Polycystin-1 causes cAMP-dependent switch from tubule to cyst formation. - Scholz, Julia; Kraus, Andre; Lueder, Dominik; Skoczynski, Kathrin; Schiffer, Mario; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (iScience, 2022)
Autosomal dominant polycystic kidney disease is the most common monogenic disease that causes end-stage renal failure. It primarily results from mutations in the PKD1 gene that encodes for Polycystin-1. How loss of Polycystin-1 translates into bilateral renal cyst development is mostly unknown. cAMP is significantly involved in cyst enlargement but its role in cyst initiation has remained elusive. Deletion of Polycystin-1 in collecting duct cells resulted in a switch from tubule to cyst formation and was accompanied by an increase in cAMP. Pharmacological elevation of cAMP in Polycystin-1-competent cells caused cyst formation, impaired plasticity, nondirectional migration, and mis-orientation, and thus strongly resembled the phenotype of Polycystin-1-deficient cells. Mis-orientation of developing tubule cells in metanephric kidneys upon loss of Polycystin-1 was phenocopied by pharmacological increase of cAMP in wildtype kidneys. In vitro, cAMP impaired tubule formation after capillary-induced injury which was further impaired by loss Polycystin-1.
EVALuna2:505609

Macrophage migration inhibitory factor is regulated by HIF-1α and cAMP and promotes renal cyst cell proliferation in a macrophage-independent manner - Safi, Wajima; Kraus, Andre; Grampp, Steffen; Schödel, Johannes; Buchholz, Björn (Journal of Molecular Medicine, 2020)
Abstract: Progressive cyst growth leads to decline of renal function in polycystic kidney disease. Macrophage migration inhibitory factor (MIF) was found to be upregulated in cyst-lining cells in a mouse model of polycystic kidney disease and to promote cyst growth. In addition, MIF can be secreted by tubular cells and may contribute to cyst growth in an autocrine manner. However, the underlying mechanisms leading to induction of MIF in cyst-lining cells remained elusive. Here, we demonstrate that hypoxia-inducible transcription factor (HIF) 1α upregulates MIF in cyst-lining cells in a tubule-specific PKD1 knockout mouse. Pharmacological stabilization of HIF-1α resulted in significant increase of MIF in cyst epithelial cells whereas tubule-specific knockout of HIF-1α prevented MIF upregulation. Identical regulation could be found for ABCA1, which has been shown to act as a transport protein for MIF. Furthermore, we show that MIF and ABCA1 are direct target genes of HIF-1α in human primary tubular cells. Next to HIF-1α and hypoxia, we found MIF being additionally regulated by cAMP which is a strong promotor of cyst growth. In line with these findings, HIF-1α- and cAMP-dependent in vitro cyst growth could be decreased by the MIF-inhibitor ISO-1 which resulted in reduced cyst cell proliferation. In conclusion, HIF-1α and cAMP regulate MIF in primary tubular cells and cyst-lining epithelial cells, and MIF promotes cyst growth in the absence of macrophages. In line with these findings, the MIF inhibitor ISO-1 attenuates HIF-1α- and cAMP-dependent in vitro cyst enlargement. Key messages: • MIF is upregulated in cyst-lining cells in a polycystic kidney disease mouse model. • MIF upregulation is mediated by hypoxia-inducible transcription factor (HIF) 1α. • ABCA1, transport protein for MIF, is also regulated by HIF-1α in vitro and in vivo. • MIF is additionally regulated by cAMP, a strong promotor of cyst growth. • MIF-inhibitor ISO-1 reduces HIF-1α- and cAMP-dependent cyst growth.
CRIS-Team Scopus Importer:2020-09-11
Keywords: cAMP; Hypoxia-inducible factor 1α; Macrophage migration inhibitory factor; Polycystic kidney disease

P2Y2R and Cyst Growth in Polycystic Kidney Disease. - Kraus, Andre; Skoczynski, Kathrin; Brötsch, Martin; Burzlaff, Nicolai; Leipziger, Jens; Schiffer, Mario; Büttner-Herold, Maike; Buchholz, Björn (Journal of the American Society of Nephrology, 2024)
EVALuna2:569374

P2Y2R is a direct target of HIF-1α and mediates secretion-dependent cyst growth of renal cyst-forming epithelial cells - Kraus, Andre; Grampp, Steffen; Goppelt-Strübe, Margarete; Schreiber, Rainer; Kunzelmann, Karl; Peters, Dorien J. M.; Leipziger, Jens; Schley, Gunnar; Schödel, Johannes; Eckardt, Kai-Uwe; Buchholz, Björn (Purinergic Signalling, 2016)
Polycystic kidney diseases are characterized by numerous renal cysts that continuously enlarge resulting in compression of intact nephrons and tissue hypoxia. Recently, we have shown that hypoxia-inducible factor (HIF)-1 alpha promotes secretion-dependent cyst expansion, presumably by transcriptional regulation of proteins that are involved in calcium-activated chloride secretion. Here, we report that HIF-1 alpha directly activates expression of the purinergic receptor P2Y2R in human primary renal tubular cells. In addition, we found that P2Y2R is highly expressed in cyst-lining cells of human ADPKD kidneys as well as PKD1 orthologous mouse kidneys. Knockdown of P2Y2R in renal collecting duct cells inhibited calcium-dependent chloride secretion in Ussing chamber analyses. In line with these findings, knockdown of P2Y2R retarded cyst expansion in vitro and prevented ATP- and HIF-1 alpha-dependent cyst growth. In conclusion, P2Y2R mediates ATP-dependent cyst growth and is transcriptionally regulated by HIF-1 alpha. These findings provide further mechanistic evidence on how hypoxia promotes cyst growth.
EVALuna2:3913
Keywords: Polycystic kidney disease; Cyst growth; Chloride secretion; ATP; P2Y2R; Hypoxia; HIF-1 alpha

Pathogenic Relationships in Cystic Fibrosis and Renal Diseases: CFTR, SLC26A9 and Anoctamins - Kunzelmann, Karl; Ousingsawat, Jiraporn; Kraus, Andre; Park, Julien H.; Marquardt, Thorsten; Schreiber, Rainer; Buchholz, Björn (International Journal of Molecular Sciences, 2023)
The Cl−-transporting proteins CFTR, SLC26A9, and anoctamin (ANO1; ANO6) appear to have more in common than initially suspected, as they all participate in the pathogenic process and clinical outcomes of airway and renal diseases. In the present review, we will therefore concentrate on recent findings concerning electrolyte transport in the airways and kidneys, and the role of CFTR, SLC26A9, and the anoctamins ANO1 and ANO6. Special emphasis will be placed on cystic fibrosis and asthma, as well as renal alkalosis and polycystic kidney disease. In essence, we will summarize recent evidence indicating that CFTR is the only relevant secretory Cl− channel in airways under basal (nonstimulated) conditions and after stimulation by secretagogues. Information is provided on the expressions of ANO1 and ANO6, which are important for the correct expression and function of CFTR. In addition, there is evidence that the Cl− transporter SLC26A9 expressed in the airways may have a reabsorptive rather than a Cl−-secretory function. In the renal collecting ducts, bicarbonate secretion occurs through a synergistic action of CFTR and the Cl−/HCO3− transporter SLC26A4 (pendrin), which is probably supported by ANO1. Finally, in autosomal dominant polycystic kidney disease (ADPKD), the secretory function of CFTR in renal cyst formation may have been overestimated, whereas ANO1 and ANO6 have now been shown to be crucial in ADPKD and therefore represent new pharmacological targets for the treatment of polycystic kidney disease.
CRIS-Team Scopus Importer:2023-09-15
Keywords: anoctamin; CFTR; pendrin; SLC26A9; TMEM16A; TMEM16F

The chloride channel CFTR is not required for cyst growth in an ADPKD mouse model - Talbi, Khaoula; Cabrita, Inês; Kraus, Andre; Hofmann, Sascha; Skoczynski, Kathrin; Kunzelmann, Karl; Buchholz, Björn; Schreiber, Rainer (The FASEB Journal, 2021)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by the development of bilateral renal cysts which enlarge continuously, leading to compression of adjacent intact nephrons. The growing cysts lead to a progressive decline in renal function. Cyst growth is driven by enhanced cell proliferation and chloride secretion into the cyst lumen. Chloride secretion is believed to occur mainly by the cAMP-activated cystic fibrosis transmembrane conductance regulator (CFTR), with some contribution by the calcium-activated chloride channel TMEM16A. However, our previous work suggested TMEM16A as a major factor for renal cyst formation. The contribution of CFTR to cyst formation has never been demonstrated in an adult ADPKD mouse model. We used mice with an inducible tubule-specific Pkd1 knockout, which consistently develop polycystic kidneys upon deletion of Pkd1. Cellular properties, ion currents, and cyst development in these mice were compared with that of mice carrying a co-deletion of Pkd1 and Cftr. Knockout of Cftr did not reveal any significant impact on cyst formation in the ADPKD mouse model. Furthermore, knockout of Cftr did not attenuate the largely augmented cell proliferation observed in Pkd1 knockout kidneys. Patch clamp analysis on primary renal epithelial cells lacking expression of Pkd1 indicated an only marginal contribution of CFTR to whole cell Cl− currents, which were clearly dominated by calcium-activated TMEM16A currents. In conclusion, CFTR does not essentially contribute to renal cyst formation in mice caused by deletion of Pkd1. Enhanced cell proliferation and chloride secretion is caused primarily by upregulation of the calcium-activated chloride channel TMEM16A.
CRIS-Team Scopus Importer:2021-10-08
Keywords: ADPKD; CFTR; cyst growth; proliferation; TMEM16A

The extracellular matrix protein fibronectin promotes metanephric kidney development - Skoczynski, Kathrin; Kraus, Andre; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute; Schiffer, Mario; Hermann, Kristina; Herrnberger-Eimer, Leonie; Tamm, Ernst R.; Buchholz, Björn (Pflügers Archiv: European Journal of Physiology, 2024)
Complex interactions of the branching ureteric bud (UB) and surrounding mesenchymal cells during metanephric kidney development determine the final number of nephrons. Impaired nephron endowment predisposes to arterial hypertension and chronic kidney disease. In the kidney, extracellular matrix (ECM) proteins are usually regarded as acellular scaffolds or as the common histological end-point of chronic kidney diseases. Since only little is known about their physiological role in kidney development, we aimed for analyzing the expression and role of fibronectin. In mouse, fibronectin was expressed during all stages of kidney development with significant changes over time. At embryonic day (E) 12.5 and E13.5, fibronectin lined the UB epithelium, which became less pronounced at E16.5 and then switched to a glomerular expression in the postnatal and adult kidneys. Similar results were obtained in human kidneys. Deletion of fibronectin at E13.5 in cultured metanephric mouse kidneys resulted in reduced kidney sizes and impaired glomerulogenesis following reduced cell proliferation and branching of the UB epithelium. Fibronectin colocalized with alpha 8 integrin and fibronectin loss caused a reduction in alpha 8 integrin expression, release of glial-derived neurotrophic factor and expression of Wnt11, both of which are promoters of UB branching. In conclusion, the ECM protein fibronectin acts as a regulator of kidney development and is a determinant of the final nephron number.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Alpha 8 integrin; Branching; Fibronectin; Kidney development; Nephron number

The impact of chloride secretion on the progression of polycystic kidney disease - Kraus, Andre; Faria, D.; Schley, Gunnar; Schödel, Johannes; Grampp, S.; Peters, D. J.; Schreiber, R.; Kunzelmann, K.; Eckardt, Kai-Uwe; Buchholz, Björn (Acta Physiologica, 2019)

The impact of chloride secretion on the progression of polycystic kidney disease - Kraus, Andre; Faria, D.; Schley, Gunnar; Schödel, Johannes; Grampp, S.; Peters, D. J.; Schreiber, R.; Kunzelmann, K.; Eckardt, K. -U.; Buchholz, B. (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18

Ultra high frequency ultrasound enables real-time visualization of blood supply from chorioallantoic membrane to human autosomal dominant polycystic kidney tissue - Schueler, Jan; Kuenzel, Jonas; Thuesing, Anna; Pion, Eric; Behncke, Rose Yinghan; Haegerling, Rene; Fuchs, Dieter; Kraus, Andre; Buchholz, Björn; Huang, Boqiang; Merhof, Dorit; Werner, Jens M.; et al. (Scientific Reports, 2024)
Ultra high frequency (UHF) ultrasound enables the visualization of very small structures that cannot be detected by conventional ultrasound. The utilization of UHF imaging as a new imaging technique for the 3D-in-vivo chorioallantoic membrane (CAM) model can facilitate new insights into tissue perfusion and survival. Therefore, human renal cystic tissue was grafted onto the CAM and examined using UHF ultrasound imaging. Due to the unprecedented resolution of UHF ultrasound, it was possible to visualize microvessels, their development, and the formation of anastomoses. This enabled the observation of anastomoses between human and chicken vessels only 12 h after transplantation. These observations were validated by 3D reconstructions from a light sheet microscopy image stack, indocyanine green angiography, and histological analysis. Contrary to the assumption that the nutrient supply of the human cystic tissue and the gas exchange happens through diffusion from CAM vessels, this study shows that the vasculature of the human cystic tissue is directly connected to the blood vessels of the CAM and perfusion is established within a short period. Therefore, this in-vivo model combined with UHF imaging appears to be the ideal platform for studying the effects of intravenously applied therapeutics to inhibit renal cyst growth.
CRIS-Team Scopus Importer:2024-05-10